Fine Needle Aspiration Diagnosed Skin Metastasis in a Young Man with Rectal Cancer - Nasrolahi, Hamid; Geramizadeh, Bita; MoaddabShoar, Leila; Hamedi, Seyed Hasan; MohammadianPanah, Mohammad; Omidvari, Shapour; Ansari, Mansour; Ahmadloo, Niloofar; Mosalaei, Ahmad (Reports of Radiotherapy and Oncology, 2023)
Introduction: Although colon cancer is one of the most common human cancers, skin metastasis in this disease is rare and necessitates pathological confirmation. Report of the case: Herein we present a 33 year old man with rectal cancer with ascites. Six cycles of Oxaliplatin based chemotherapy were given. The ascites improved. After three weeks, skin lesions appeared in the upper trunk, both chest wall and back, with extension to the anterior neck Fine Needle Aspiration from the lesions showed malignancy and second line chemotherapy was started. Although the skin lesions showed partial response, unfortunately, the patient died after the fourth chemotherapy injection. Conclusion: Skin metastasis in colorectal cancer, although rare, is a devastating sign, and a careful dermatologic examination should be included in these patients’ follow up visits.